2008
DOI: 10.2174/1874205x00802010051
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin and Metal Levels as Risk Factors for Amyotrophic Lateral Sclerosis

Abstract: Metal toxicity has been identified as a possible risk factor for amyotrophic lateral sclerosis (ALS) and other neurodegenerative disorders. We conducted a retrospective chart review of urinary, hair and blood metal levels and serum ferritin in 321 people with ALS seen over a ten-year period at the Massachusetts General Hospital (MGH). We found that hair lead levels and serum ferritin levels were elevated in ALS patients compared to published normal values. Metal levels of arsenic, lead, mercury, cadmium, thall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 40 publications
5
41
1
2
Order By: Relevance
“…Before the discovery linking SOD1 and ALS, epidemiological studies on ALS suggested that exposure to metallic trace elements was a significant factor among many other environmental factors such as viruses, strenuous exercise, and excitotoxic chemicals that may have a role in ALS etiology (4 -6). Studies on exposure to and tissue accumulation of metallic elements in ALS patients show a correlative yet unspecified role for many metals including copper and zinc in SOD1-related ALS (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Over the years, a number of hypotheses relating metal toxicity to ALS have been proposed.…”
mentioning
confidence: 99%
“…Before the discovery linking SOD1 and ALS, epidemiological studies on ALS suggested that exposure to metallic trace elements was a significant factor among many other environmental factors such as viruses, strenuous exercise, and excitotoxic chemicals that may have a role in ALS etiology (4 -6). Studies on exposure to and tissue accumulation of metallic elements in ALS patients show a correlative yet unspecified role for many metals including copper and zinc in SOD1-related ALS (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Over the years, a number of hypotheses relating metal toxicity to ALS have been proposed.…”
mentioning
confidence: 99%
“…Specifically, injection of Al-containing adjuvants at levels comparable to those that are administered to human adults resulted in the death of motor neurons, impairments in motor function, decrements in spatial memory capacity in young mice and significant increases in activated astrocytes and microglia (Petrik et al, 2007;Shaw and Petrik, 2009). Blood and urine levels of Al may also be elevated in ALS (Perl et al, 1982) but there is disagreement concerning this (Qureshi et al, 2008).…”
Section: Link Between Aluminum Exposure and Neurodegenerative Conditimentioning
confidence: 99%
“…38 Metal toksisitesinin ALS ve diğer nörodejeneratif hastalıklarda risk faktörü olduğu düşünülse de 321 hastanın değerlendirildiği retrospektif bir çalışmada, idrar Al düzeylerinin normal sınırlar içinde olduğu bildirilmiştir. 39 ALS tanısı olan beş hastanın ventral servikal spinal kord örnekleri alınarak Al, Ca ve Fe düzeyleri ölçüldüğünde, Al düzeylerinin kontrole göre fark göstermediği, sadece Fe düzeylerin yük-sek olduğu saptanmıştır. 40 Benzer şekilde 100 ALS ve 100 sağlıklı kontrolde yapılan saç analizlerinde, vanadyum, Al, Mg ve Mn düzeylerinde anlamlı bir fark görülmemiştir.…”
Section: Amyotrofi̇k Lateral Sklerozunclassified